Analysis of the impact of strategic diversification on corporate performance in the global competitive market - Al-Shuwaikhat, Sadiq Ali Mubarak; Al Tuwaym, Haya Ibrahim Abdulrahman; Al-Dawsari, Sara Saad (Journal of Economic, Administrative and Legal Sciences, 2024)
Strategic diversification is a cornerstone of corporate strategies in the Kingdom of Saudi Arabia (KSA) within the global competitive market. It involves developing diverse products and services, entering new markets, and investing in advanced technologies and innovations to expand the scope of business and improve performance. This research aims to shed light on the importance of strategic diversification as a key element in the strategies of global companies and to examine its potential impact on their performance in the context of global competition, which is a key factor for excellence and survival. The research explores the impact of this diversification on the capabilities of manufacturing companies in the KSA and identifies the impact of this relationship on their overall performance, analyzing strategic diversification to enhance innovation capabilities within them. It also examines the factors of diversification in light of the rapid transformations in the global market. The research adopted a descriptive analytical approach to examine the theoretical foundations related to the topic and to conduct a field study on a sample of (192) respondents. The electronic questionnaire was distributed to the sample to be answered, in addition to using a Likert scale. The statistical program SPSS was used to analyze the study data. The research reached a set of results, including: There is a high level of application of strategic diversification in food industry companies in the KSA from the perspective of the sample individuals, as the arithmetic mean value reached 4.178 with a standard deviation of 0.745., There is a very high level of performance of food industry companies in the KSA in the global competitive market from the perspective of the sample individuals, as the arithmetic mean value reached 4.357 with a standard deviation of 0.626.
Keywords: Strategic diversification; global competition; Market competition; flexibility and adaptation; innovation